2014
DOI: 10.2478/s11535-014-0330-1
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of melatonin applied to Vigna radiata L. seeds in plant response to chilling stress

Abstract: The impact of melatonin (50 µM L−1) applied to Vigna radiata seeds by hydro-priming on phenolic content, L-phenylalanine ammonialyase (PAL) activity, MEL level, antioxidant properties of ethanol extracts as well as electrolyte leakage from chilled and re-warmed Vigna radiata roots of seedlings were examined. Seedlings obtained from non-primed seeds, hydro-primed and hydro-primed with MEL were investigated after 2 days of chilling and 2 days of re-warming. At 25°C, the level of MEL in roots derived from seeds h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 60 publications
(80 reference statements)
1
16
0
Order By: Relevance
“…The melatonin content of MT-1 and MT-2 treated grape berries was 7.93 and 8.44 ng/L repectively, increasing the content by 8.2% and 15.1% as compared with the control. The increasement in melatonin content probably due to exogenous melatonin applied was consistent with earlier reports on the roots of Vigna radiata seedlings (Szafrańska et al, 2014), which indicated that melatonin applied to the seeds of V. radiata can improve the melatonin content. So we can infer that the exogenous melatonin applied to pre-veraison berries stimulated the concentration of melatonin in grape berries.…”
Section: Effect Of Melatonin Treatment On Individual Anthocyanin Phensupporting
confidence: 91%
See 1 more Smart Citation
“…The melatonin content of MT-1 and MT-2 treated grape berries was 7.93 and 8.44 ng/L repectively, increasing the content by 8.2% and 15.1% as compared with the control. The increasement in melatonin content probably due to exogenous melatonin applied was consistent with earlier reports on the roots of Vigna radiata seedlings (Szafrańska et al, 2014), which indicated that melatonin applied to the seeds of V. radiata can improve the melatonin content. So we can infer that the exogenous melatonin applied to pre-veraison berries stimulated the concentration of melatonin in grape berries.…”
Section: Effect Of Melatonin Treatment On Individual Anthocyanin Phensupporting
confidence: 91%
“…The activity of this enzyme is affected by various biotic and abiotic stresses. Previous research on the seeds of Vigna radiate L. seeds indicated that extrogenous melatonin increased the activity of PAL, accompanied by the induced accumulation of total phenolics and increasement of antioxidant capacity (Szafrańska et al, 2014). However, as a new phytohormone, the effect of melatonin on the phenolic composition of grape berries and wine remains unclear.…”
Section: Introductionmentioning
confidence: 98%
“…The beneficial effects of seed priming on their resistance to environmental stresses is documented (Jisha et al, 2013). Our data indicate that the positive effects of pre-sowing melatonin application by priming relates not only to seed quality (higher germination and vigor under suboptimal conditions) but also to seedling development, plant growth and product yield (Janas et al, 2009; Posmyk et al, 2009a; Szafrańska et al, 2012, 2013, 2014). …”
Section: Introductionmentioning
confidence: 72%
“…In relation to this, exogenous melatonin application into the seeds using different priming methods has proven highly effective (Posmyk et al, 2008, 2009a,b; Janas et al, 2009; Szafrańska et al, 2012, 2013, 2014; Kołodziejczyk et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Melatonin concentrations were chosen as optimal, on the basis of previous experiments (Szafrańska et al, 2014). A fungicide, Thiuram (Organica-Sarzyna, Poland), was used for seed sterilization, and thereafter they were placed in plastic boxes with cottonwool moistened with distilled water and germinated at 25°C for 3 days.…”
Section: Methodsmentioning
confidence: 99%